2010
DOI: 10.1007/s11368-010-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequential solidification/stabilization and thermal process under vacuum for the treatment of mercury in sediments

Abstract: Purpose Millions of cubic meters of sediments are dredged every year in the world. About 10–20%onweight basis of this material is contaminated by organic and/or inorganic pollutants. This work presents the laboratory tests performed to study a system for the remediation and reuse of mercurycontaminated sediments. The treatment is based on a cementbased granulation step (solidification/stabilization (S/S)), followed by a thermal process under vacuum during which volatile and semi-volatile compounds are removed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…PAH, TPH and heavy metal concentrations were below the Italian regulatory limits, whereas the Hg level was much higher than the limit of 1 mg kg −1 . Physical characterization and the nature of the contamination found are consistent with characteristics of coastal sediments of the SW zone of Augusta Bay [4,24,43]. In terms of dielectric properties, the observed relatively high dielectric constant ( ') and loss factor ( ") of 11.3 and 0.6, respectively, are due to the high percentage of CaCO3 and the presence of Al and Fe oxides in the sediment composition.…”
Section: Sediment Characterization and Hg-speciationsupporting
confidence: 72%
See 1 more Smart Citation
“…PAH, TPH and heavy metal concentrations were below the Italian regulatory limits, whereas the Hg level was much higher than the limit of 1 mg kg −1 . Physical characterization and the nature of the contamination found are consistent with characteristics of coastal sediments of the SW zone of Augusta Bay [4,24,43]. In terms of dielectric properties, the observed relatively high dielectric constant ( ') and loss factor ( ") of 11.3 and 0.6, respectively, are due to the high percentage of CaCO3 and the presence of Al and Fe oxides in the sediment composition.…”
Section: Sediment Characterization and Hg-speciationsupporting
confidence: 72%
“…Careghini et al [43] reported a maximum Hg removal of 63% from marine sediments dredged from Augusta Bay applying a sequential S/S and thermal process for 4 h. Similar removals were found by Comuzzi et al [64] testing a decontamination procedure of Hg-polluted dredged sludge from Marano-Grado Lagoon (NE Italy), based on cationic exchange associated with low temperature thermal desorption. Hg removals between 24 and 60% were observed when the samples were treated with a 15% solution of tetrabutyl-ammonium chloride.…”
Section: Comparison To Other Clean-up Alternativessupporting
confidence: 56%
“…Besides, thermal treatment of mercury contaminated sediments showed that the percentage of mercury removal raises with the temperature during the treatment of solid matrices [9,10]. Furthermore, the treatment of mercury wastes from the chloralkali industry showed that treatment for 1 h at 800 °C allowed for a removal efficiency above 99.7% [11].…”
Section: Open Accessmentioning
confidence: 99%
“…At the present, 57 National Priority Sites (NPSs) have been issued in Italy in order to achieve the management of the characterization and remediation procedures under the direct responsibility of the Ministry of the Environment. Twenty-nine of these sites (i.e., 60 km 2 in Brindisi, 100 km 2 in Priolo, 900 km 2 in the Sulcis area, 80 km 2 in Taranto, and 75 km 2 in the Venice lagoon) require either sediment containment or treatment activities [1]. High levels of polychlorobiphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), high molecular weight (C 12 -C 40 ) petroleum hydrocarbons, and heavy metals, such as mercury, were generally found in contaminated sediments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Technically and economically feasible treatment strategies need to be identified. The commonly employed and emerging techniques for mercury ex situ remediation are stabilisation/solidification (S/S), thermal desorption, soil washing, or phytoremediation [1]. However, these alternatives could be extremely expensive or long time requiring.…”
Section: Introductionmentioning
confidence: 99%